Unsung Freedom Fighters of the Delhi Region: दिल्ली परिक्षेत्र के गुमनाम स्वतंत्रता सेनानी - Kumar, Ankit; Poonam (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
The Delhi region has been a crucial center of the Indian freedom struggle. It gave birth to many unsung but significant freedom fighters who fiercely resisted British rule. Among them were prominent revolutionaries like Raja Nahar Singh, Master Amir Chand, Avadh Bihari, and Lala Hardayal. Raja Nahar Singh led the revolt against British authority in the Gurgaon region and sacrificed his life for the cause. Avadh Bihari supported the rebellion through covert operations, organization, and ideology. Lala Hardayal presented the Indian national movement on a global platform. Their sacrifices prove the saying, "The revolution brings joyful change, but the pain of its birth is borne by the revolutionary alone." This research also highlights some freedom fighters who are still alive today. Their relentless spirit and sacrifices have made the “Delhi region” a significant land in the history of India’s independence struggle. Abstract in Hindi Language: दिल्ली परिक्षेत्र, भारतीय स्वतंत्रता संग्राम का एक महत्वपूर्ण केंद्र रहा है। इस क्षेत्र ने कई गुमनाम लेकिन महत्वपूर्ण स्वतंत्रता सेनानियों को जन्म दिया, जिन्होंने ब्रिटिश शासन के खिलाफ मजबूती से संघर्ष किया। इनमें राजा नाहर सिंह, मास्टर अमीरचंद, अवध बिहारी, लाला हरदयाल जैसे प्रमुख सेनानी शामिल हैं। राजा नाहर सिंह ने गुड़गांव क्षेत्र में ब्रिटिश सत्ता के खिलाफ संग्राम का नेतृत्व किया और बलिदान दिया। वहीं अवध बिहारी ने विद्रोहियों के लिए गुप्त समर्थन, संगठन और विचारधारा के माध्यम से संघर्ष को मजबूती दी। लाला हरदयाल ने भारतीय राष्ट्रीय आंदोलन को वैश्विक मंच पर प्रस्तुत किया। इन क्रांतिकारियों का त्याग और बलिदान यह प्रमाणित करता है कि "क्रांति जिस सुखमय परिवर्तन को जन्म देती है, उसकी प्रसव पीड़ा क्रांतिकारी ही सहता है।" उक्त शोध पत्रिका में कुछ ऐसे स्वतंत्रता सेनानियों का भी उल्लेख हुआ है, जो वर्तमान में भी जीवित है। इन सेनानियों की संघर्षशीलता और बलिदान ने “दिल्ली परिक्षेत्र” को स्वतंत्रता संग्राम की एक महत्वपूर्ण ‘भूमि’ बना दिया। Keywords: दिल्ली परिक्षेत्र, स्वतंत्रता सेनानी, लाला हरदयाल, मास्टर अमीरचंद, अवध बिहारी, क्रांतिकारी